2003
DOI: 10.1046/j.1365-2133.2003.05378.x
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of the Dermatology Life Quality Index to clinical change in patients with psoriasis

Abstract: This study contributes to building evidence of validity for the DLQI, because the instrument demonstrated the ability to detect small but meaningful changes in clinical status over time in a large sample of patients with psoriasis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
54
0
3

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(63 citation statements)
references
References 23 publications
6
54
0
3
Order By: Relevance
“…Results of the present study found that patients with moderate to severe psoriasis had poor to fair QoL, while patients with mild psoriasis had good QoL in all domains except the financial, which was poor for all levels of disease severity, nevertheless these results were insignificant. These findings were comparable to previous studies, which established a good correlations between disease severity and QoL (32)(33)(34)(35)(36) . However, the current study findings differ from those findings of Perira da Silva et al (2013) who mentioned that severity of the disease as evaluated by health practitioners was not associated with impaired QoL reported by the patients (37) .…”
Section: Discussionsupporting
confidence: 82%
“…Results of the present study found that patients with moderate to severe psoriasis had poor to fair QoL, while patients with mild psoriasis had good QoL in all domains except the financial, which was poor for all levels of disease severity, nevertheless these results were insignificant. These findings were comparable to previous studies, which established a good correlations between disease severity and QoL (32)(33)(34)(35)(36) . However, the current study findings differ from those findings of Perira da Silva et al (2013) who mentioned that severity of the disease as evaluated by health practitioners was not associated with impaired QoL reported by the patients (37) .…”
Section: Discussionsupporting
confidence: 82%
“…The mean DLQI score reduction of 1.9 observed in leflunomide-treated patients is similar to the reduction of 2.1 observed in psoriasis patients treated for 1 month with topical corticosteroids (45). In a recent study of DLQI scores in patients with severe psoriasis requiring hospital admission, mean DLQI score reductions of 3.0 were associated with improved clinical status (46). Although the mean DLQI score change was somewhat lower in the present study, the DLQI has been found to have a substantial "floor effect" (i.e., a high number of patients with the lowest possible score) in patients with milder psoriasis (45); therefore, clinically significant change in this population would be expected to result in smaller DLQI score reductions.…”
Section: Discussionsupporting
confidence: 58%
“…The DLQI has been used in at least 29 studies in psoriasis [15], representing use in 10 countries and is sensitive to clinical change [16]. General measures such as the SF-36 [17] and Sickness Impact Profile [18] have also been used.…”
Section: Other Measures Available To Assess Quality Of Life Changes Imentioning
confidence: 99%